Reconstruction of Pretrial Institution Function in Supervising Investigator Authorization Based on Justice Value with Moderating Role of Supply Chain Management - Johny Khoesoema Hioe; Anis Mashdurohatun; Gunarto .; Irwan Jasa Tarigan (International Journal of Supply Chain Management, 2020)
The weaknesses of the pretrial concept are revealed in many academic discussions and directly felt by practitioners and pretrial applicants. Many things are hampered to cause pretrial as a complaint mechanism to be unfair and very ineffective. This research uses a normative juridical approach, namely by studying or analyzing secondary data in the form of secondary legal materials by understanding the law as a set of rules or positive norms in the legislation system that regulates human life. The results of the study resulted that pre-trial weaknesses in the criminal justice system that are just include Pre-Judicial Authority Only Post Factum, Detention Testing: Limited Only Administrative Review and Objectives of Detention Objectives, Passive Judges' Attitudes in Pre-Trial, Pre-Trial Death Eliminating Suspect Rights, Pre-Judicial Procedure Issues: Between Civil, Criminal and Minus Rules, Pre-Judicial Case Management and Pre-Trial Timeliness, Pre-Trial Depends Very Dependent on the Existence of Attorney. It further concludes that supply chain Information management system positively moderates the relation between pretrial function, investigator function and justice value.